The Count of Monte Cristo. - Reynolds, Kevin (New Manila, Quezon City : Viva Video, 2002)
Jim Caviezel (Angel Eyes) and Guy Pearce (L.A. Confidential), two of the hottest young actors today, give sizzling performances alongside Richard Harris ( Harry Potter) in THE COUNT OF MONTE CRISTO - the greatest tale of betrayal, adventure and revenge the word has ever known. When the dashing and guileless Edmond Dantes (Caviezel) is betrayed by his friend (Pearce) and wrongly imprisoned, he becomes consumed by thoughts of vengeance. After a miraculous escape, her transforms himself into the mysterious and wealthy Count of Monte Cristo, insinuates himself into the French nobility and puts his cunning plan of revenge into action. From the director of Robin Hood: Price Of Thieves and the producers of The Sixth Sense, this swashbuckling thriller will have you sitting on the ounce of revenge is exacted.